METHOD OF APPLYING COMPARATIVE RECEPTION FOR ANALYSIS OF EVERYDAY VOCABULARY FROM TEXT (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article analyzes the methodology for using the comparative technique as a way to expand interpretive capabilities when analyzing text for the study of everyday lexical words and their influence on the perception of Russian language phenomena by national and foreign students. The main task is also considered - increasing the level of use and comparison of communicative competence, the formation of stable skills and abilities that allow the correct use of everyday vocabulary in various communication situations, the formation of a culture of personal communication, which is one of the main tasks of education.